Digital Payments and Regional Financial Intermediation - Fariza Raz, Arisyi (Otoritas Jasa Keuangan, 2024)
The development of information and communication technology (ICT) in the banking sector leads to the proliferation of digital payments. Using Indonesia’s sub-national (provincial) banking data, we examine how bank loans and savings respond to digital payments. Our results show that digital payments increase transaction efficiency, boost consumption, and ultimately contribute positively to regional output. Digital payments also provide depositors with various investment options that can be accessed from mobile banking apps, thus increasing these investments while decreasing bank savings. These findings provide insights into the positive effects of digital payments on regional financial intermediation and development.